'We don't tell people what to do': ethical practice and Indigenous health promotion. (25th November 2015) - McPhail‐Bell, Karen; Bond, Chelsea; Brough, Mark; Fredericks, Bronwyn
Abstract : Health promotion aspires to work in empowering, participatory ways, with the goal of supporting people to increase control over their health. However, buried in this goal is an ethical tension: while increasing people's autonomy, health promotion also imposes a particular, health promotion‐sanctioned version of what is good. This tension positions practitioners precariously, where the ethos of empowerment risks increasing health promotion's paternalistic control over people, rather than people's control over their own health. Herein we argue that this ethical tension is amplified in Indigenous Australia, where colonial processes of control over Indigenous lands, lives and cultures are indistinguishable from contemporary health promotion 'interventions'. Moreover, the potential stigmatisation produced in any paternalistic acts 'done for their own good' cannot be assumed to have evaporated within the self‐proclaimed 'empowering' narratives of health promotion. This issue's guest editor's call for health promotion to engage 'with politics and with philosophical ideas about the state and the citizen' is particularly relevant in an Indigenous Australian context. Indigenous Australians continue to experience health promotion as a moral project of control through intervention, which contradicts health promotion's central goal of empowerment. Therefore, Indigenous health promotion is an invaluable site for discussion and analysis of health promotion's broader ethical tensions. Given the persistent and alarming Indigenous health inequalities, this paper calls for systematic ethical reflection in order to redress health promotion's general failure to reduce health inequalities experienced by Indigenous Australians.